Detecting senescence: a new method for an old pigment - Salmonowicz, Hanna (Aging Cell, 2017)
Cellular senescence is a state of irreversible cell cycle arrest induced by different types of cellular stresses. The field of senescence has made significant advances in the understanding of many of the mechanisms governing this phenomenon; however, a universal biomarker that unambiguously distinguishes senescent from proliferating cells has not been found. In this issue of Aging Cell, Evangelou and colleagues developed a sensitive method for identification of senescent cells in different types of biological material based on the detection of lipofuscin using an analogue of Sudan Black B (SBB) histochemical dye coupled with biotin, which they named GL13. The authors propose that this method is more sensitive and versatile than using SBB alone. Lipofuscin, a nondegradable oxidation product of lipids, proteins and metals, is found in senescent cells. Detection of lipofuscin using GL13 staining may be a more feasible method than others currently used for identification of senescent cells both in cell culture and tissues.